2000
DOI: 10.3390/50100051
|View full text |Cite
|
Sign up to set email alerts
|

A Short Review on Cardiotonic Steroids and Their Aminoguanidine Analogues

Abstract: A short review on cardiotonic steroids and their analogues is presented. The natural, semisynthetic and synthetic derivatives, as well as their mechanism of action and structure-activity relationships are shown, with a special reference to aminoguanidine derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 90 publications
(59 reference statements)
2
85
0
Order By: Relevance
“…These headings were interchanged with the word "herbal," and limits were placed on keywords so that only human cases were brought forward. Using a list contained within a review by Melero et al of CAS, we constructed our list of CAS sources [9]. Papers published in languages other than English were translated.…”
Section: Methodsmentioning
confidence: 99%
“…These headings were interchanged with the word "herbal," and limits were placed on keywords so that only human cases were brought forward. Using a list contained within a review by Melero et al of CAS, we constructed our list of CAS sources [9]. Papers published in languages other than English were translated.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, this steroid core is double-substituted with an unsaturated lactone ring at position 17 and a sugar portion at position 3; and this lactone moiety of cardiac glycosides is critical for their potent inhibition of Na + /K + -ATPase. Although the sugar moiety does not greatly influence their biological activity, the addition of sugars to the steroid core affects the pharmacodynamic and pharmacokinetic profile of each glycoside [28] .…”
Section: Introductionmentioning
confidence: 99%
“…9,10) Thus far, the biological actions of cardenolide aglycones on the NF-κB-dependent gene expression induced by proinflammatory cytokines have been poorly characterized. We found that ouabagenin, digitoxigenin, and digoxigenin inhibit the TNF-α-induced ICAM-1 expression.…”
mentioning
confidence: 99%
“…8) Cardiac glycosides are a family of compounds that function as allosteric inhibitors of Na + /K + -ATPase. 9) Cardiac glycosides possess common structures, including a steroid core, an unsaturated lactone ring, and a sugar moiety, and are classified into two groups: cardenolides (five-membered butyrolactone ring) and bufadienolides (six-membered pyrone ring). 10,11) It has been reported that the cardenolide glycoside ouabain is able to activate the NF-κB signaling pathway at concentrations that do not inhibit Na + /K + -ATPase activity.…”
mentioning
confidence: 99%